Z세대 중국인 유학생의 유학동기가 진로결정수준에 미치는 영향 - 디지털역량의 매개효과 - 장위건(Wei-Keon Zhang), 홍명수(Myung-Su Hong) (중국학(구중국어문론집), 2025)
본 연구는 중국 Z세대의 특성 및 유학동기를 살펴보고, 내적·외적인 유학동기가진로결정수준에 미치는 영향을 분석하여 디지털 역량이 유학동기와 진로결정 간에어떠한 매개적 역할을 수행하는지를 실증적으로 고찰하였다. 한국 내 중국인 유학생232명을 대상으로 설문조사를 실시하였고, SmartPLS 4.0을 활용하여 구조방정식 모형 분석을 수행한 결과, 내적·외적 유학동기는 모두 진로결정수준에 유의한 영향을미치는 것으로 나타났으며, 디지털 역량은 이 관계를 유의미하게 매개하는 변수로확인되었다. 연구결과는 한국 대학이 유학생 진로지도를 보다 실질적으로 운영하기위한 정책 수립에 이론적·실무적 기반을 제공하며, Z세대 유학생의 특성을 반영한맞춤형 진로 설계, 디지털 기반 진로 프로그램의 개발, 그리고 유학 후 취업, 창업, 진학을 위한 전략적 지원체계 구축의 필요성을 시사한다. This study aims to describe the characteristics and study abroad motivations of Generation Z, analyse the influence of study abroad motivations (intrinsic and extrinsic) on career decisions, and empirically examine whether digital competencies play a mediating role between study abroad motivations and career decisions. A survey was conducted among 232 Chinese international students living in Korea, and structural equation model analysis was conducted using SmartPLS 4.0. The results showed that both intrinsic and extrinsic study abroad motivations had a significant impact on career decisions, and digital competence was found to be a significant mediator of this relationship. In particular, international students with extrinsic motivation tended to make more specific career decisions by utilising digital resources. These findings provide theoretical and practical basis for the establishment of international student career policies in Korean universities and suggest the need to design customized career paths that reflect the characteristics of Generation Z international students, develop digitally-based career programmes, and establish a strategic support system for employment, entrepreneurship, and further education after studying abroad. They also serve as a basis for emphasising the importance of international students’ ability to objectively reflect on their motivations for studying abroad and to design career paths that utilise digital competencies as a strategic tool. KCI Citation Count: 0